2016
DOI: 10.1007/s00394-016-1343-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac changes in apoptosis, inflammation, oxidative stress, and nitric oxide system induced by prenatal and postnatal zinc deficiency in male and female rats

Abstract: Prenatal and postnatal zinc deficiency induces alterations in cardiac apoptotic, inflammatory, oxidative, and nitric oxide pathways that could predispose the onset of cardiovascular diseases in adult life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…Although excessive NO is cytotoxic to cancer cells [27], physiological level of intracellular NO is essential for cell survival and proliferation [60]. Recently, Juriol et al demonstrate that zinc deficiency activates apoptotic and inflammatory processes with decreased nitric oxide synthase activity in cardiac tissue of rats [53]. In the present study, we found that TPEN induces apoptosis of NB4 APL cells by downregulating intracellular NO signaling.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Although excessive NO is cytotoxic to cancer cells [27], physiological level of intracellular NO is essential for cell survival and proliferation [60]. Recently, Juriol et al demonstrate that zinc deficiency activates apoptotic and inflammatory processes with decreased nitric oxide synthase activity in cardiac tissue of rats [53]. In the present study, we found that TPEN induces apoptosis of NB4 APL cells by downregulating intracellular NO signaling.…”
Section: Discussionsupporting
confidence: 63%
“…Hashemi et al demonstrate that TPEN-triggered apoptosis in MCF-7 and MDA-MB468 breast cancer cells can be reversed by the ROS scavenger NAC [47]. Juriol et al demonstrate that zinc deficiency induces NADPH oxidase-dependent superoxide anion production and increases antioxidant enzymes activity in cardiac tissue of male rats [53]. Recently, Mendivilperez et al demonstrate that TPEN induces apoptosis of acute lymphoblastic leukemia (ALL) cells independently of its zinc chelating activity.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in NO system activity was observed even when these animals were fed an adequate zinc diet during postweaning life, suggesting that this fetal injury can program the functional capacity of the NO system in adulthood. In this regard, we have demonstrated that moderate zinc deficiency during fetal and postnatal growth induces similar effects in renal and cardiac NO systems [18,21,22,56].…”
Section: Discussionmentioning
confidence: 87%
“…Lipid oxidative damage in aortic slices was evaluated by measuring the formation of 2-thiobarbituric acid reactive substances (TBARS) as previously described [22,38]. Aortic slices from 6-and 81-day-old rats of both sexes were homogenized (Pro 200, Pro Scientific Inc., Oxford, CT, USA) in 30 mM potassium phosphate buffer and 120 mM KCl, pH 7.4 (1/12 w/v), and centrifuged at 2500 rpm for 10 min at 4°C.…”
Section: Aortic Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation